Effects of olive leaf extract supplementation on systemic markers of tissue aging and remodeling in postmenopausal women: a randomized controlled trial with exploratory skin outcomes - Lasfar, Anissa; van Stratum, Sanne L. M.; Imperatrice, Maria; van Kalkeren, Colin A. J.; Scheijen, Jean L. J. M.; Schalkwijk, Casper G.; La Torre, Danique; Troost, Freddy J. (Frontiers in Nutrition, 2025)
IntroductionMenopause marks the end of a woman's reproductive cycle and is associated with a decline in estrogen levels. This hormonal shift accelerates systemic aging processes, affecting metabolic regulation, cardiovascular risk, and connective tissue integrity. Circulating biomarkers offer a non-invasive way to monitor these changes.ObjectivesThis randomized, double-blind, placebo-controlled study aimed to determine the effects of 12 weeks of olive leaf extract (OLE) supplementation on systemic markers of tissue aging and remodeling in postmenopausal women (45–70 years), and explored skin quality in a subgroup.MethodsSixty-five healthy postmenopausal women received 250 mg OLE or placebo daily. Circulating levels of elastin, collagen, hydroxyproline, matrix metalloproteinase-2 (MMP-2), advanced glycation end-products, and fasting glucose were measured. In a subgroup (n = 26), skin quality was assessed via video dermoscopy to explore the peripheral effects of OLE supplementation.ResultsElastin levels significantly increased in the placebo group while they remained stable in the OLE group [−6.3 [−12.0; −0.05], p = 0.033], but not after correction for multiple testing (padj = 0.0825). Pentosidine significantly decreased in the OLE group compared to placebo [−0.75 [−1.40; −0.11], p = 0.022], but also not after correction (padj = 0.088). Collagen, hydroxyproline, MMP-2, and glucose remained unaffected. In the exploratory skin analyses, pore number significantly decreased in the OLE group between weeks 6 and 12 [−12.9 [5.64; 20.16], p = 0.0012], while the placebo group showed no significant change [+1.25, [−6.99; 4.49], p = 0.657]. At week 12, the OLE group had a significantly lower pore number compared to placebo [−7.86, [0.64; 15.07], p = 0.034]. Surface skewness significantly decreased in the OLE group between weeks 6 and 12 [−0.32, [0.06; 0.58], p = 0.0166], while the placebo group showed no significant change [+0.1, [−0.31; 0.10], p = 0.3149]. At week 12, the OLE group showed a lower tendency toward surface skewness compared to placebo [−0.26, [−0.04; 0.56], p = 0.0847].ConclusionThe exploratory skin analyses revealed a reduction in pore number and surface skewness, suggesting that OLE may exert localized effects on skin structure. Although no statistically significant effects on systemic markers associated with tissue aging and remodeling were observed, the trends suggest potential modulation of pathways involved in extracellular matrix preservation and protein glycation. These findings warrant further investigation into both systemic and dermal effects of OLE in the context of postmenopausal aging.Clinical trial registrationThe study was registered online at ClinicalTrials.gov as NCT05744453 and was conducted at Maastricht University.